-2t=9-t

Simple and best practice solution for -2t=9-t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2t=9-t equation:


Simplifying
-2t = 9 + -1t

Solving
-2t = 9 + -1t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add 't' to each side of the equation.
-2t + t = 9 + -1t + t

Combine like terms: -2t + t = -1t
-1t = 9 + -1t + t

Combine like terms: -1t + t = 0
-1t = 9 + 0
-1t = 9

Divide each side by '-1'.
t = -9

Simplifying
t = -9

See similar equations:

| -8x+10+9x=3+x+7 | | 0.3(x-5)=0.3x+8-2+0.5 | | 4-2x-3=16 | | 1.5n=1.5 | | -19-14j=6-9j | | ax+y=10 | | -u+5=-17-18u+19u | | -4.4=0.08-0.2r | | (1-i)x-(3-i)=0 | | 16-20f=-18f | | 5x+10-30=7x-500+150 | | 8m=-10+10m | | -h-10=h+6 | | 24.33333333+-2.333333333y+4x+23=180 | | 4(5(-8)+4)=9((-8)-8) | | -10+2y=8+4y | | 7(y+1)=6y-9 | | Ht=-16t^2+35+ho | | -8t=-3-5t | | 18y-405=99 | | 10-b=9b-10 | | 4c-2=8c-10 | | 2+8=-5(6x-2) | | -p=-7-2p | | 9x-38+21y-1=180 | | 3x+-5=7x+7 | | 8+g=-10-2g | | 24+0.20x=x | | 19=(x/8) | | 2r=7+3r | | 2x+14=3x-11 | | 2v-3-11v=-6(1+19v)+-6(-18v-11) |

Equations solver categories